[Recombinant adenovirus-mediated gene transfer suppresses experimental arthritis] - Quattrocchi, E; Feldmann, M (2001)
Collagen Induced Arthritis (CIA) is a widely studied animal model to develop and test novel therapeutic approaches for treating Rheumatoid Arthritis (RA) in humans. Soluble Cytotoxic T-Lymphocyte Antigen 4 (CTLA4-Ig), which binds B7 molecule on antigen presenting cells and blocks CD28 mediated T-lymphocyte activation, has been shown to ameliorate experimental autoimmune diseases such as lupus, diabetes and CIA. Objective of our research was to investigate in vivo the effectiveness of blocking the B7/CD28 T-lymphocyte co-stimulatory pathway, utilizing a gene transfer technology, as a therapeutic strategy against CIA. Replication-deficient adenoviruses encoding a chimeric CTLA4-Ig fusion protein, or beta-galactosidase as control, have been injected intravenously once at arthritis onset. Disease activity has been monitored by the assessment of clinical score, paw thickness and type II collagen (CII) specific cellular and humoral immune responses for 21 days. The adenovirally delivered CTLA4-Ig fusion protein at a dose of 2x10^8 pfu suppressed established CIA, whereas the control beta-galactosidase did not significantly affect the disease course. CII-specific lymphocyte proliferation, IFNgamma production and anti-CII antibodies were significantly reduced by CTLA4-Ig treatment. Our results demonstrate that blockade of the B7/CD28 co-stimulatory pathway by adenovirus-mediated CTLA4-Ig gene transfer is effective in treating established CIA suggesting its potential in treating RA.